2021
DOI: 10.3390/ijms22062809
|View full text |Cite
|
Sign up to set email alerts
|

Danegaptide Prevents TGFβ1-Induced Damage in Human Proximal Tubule Epithelial Cells of the Kidney

Abstract: Chronic kidney disease (CKD) is a global health problem associated with a number of comorbidities. Recent evidence implicates increased hemichannel-mediated release of adenosine triphosphate (ATP) in the progression of tubulointerstitial fibrosis, the main underlying pathology of CKD. Here, we evaluate the effect of danegaptide on blocking hemichannel-mediated changes in the expression and function of proteins associated with disease progression in tubular epithelial kidney cells. Primary human proximal tubule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 100 publications
1
10
0
Order By: Relevance
“…Although a glomerular disease in origin, advanced stages of nephropathy are characterised by severe tubule interstitial inflammation and fibrosis [ 150 ]. Work within our laboratories links altered Cx43 expression to tubule injury in both in vitro [ 108 , 135 , 151 , 152 ] and in vivo [ 108 ] models of disease [ 153 ]. Initial observations identified an approximate 5-fold increase in Cx43 expression in biopsy material from individuals with diabetic nephropathy compared to healthy control [ 151 ], whilst paired-patch electrophysiology and ATP biosensing suggested that this increased expression was paralleled by diminished gap-junction intercellular coupling (GJIC) and increased hemichannel mediated ATP release [ 151 ].…”
Section: Cx43 Hemichannels and Treatment Of Inflammation In Diabetic Kidney Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Although a glomerular disease in origin, advanced stages of nephropathy are characterised by severe tubule interstitial inflammation and fibrosis [ 150 ]. Work within our laboratories links altered Cx43 expression to tubule injury in both in vitro [ 108 , 135 , 151 , 152 ] and in vivo [ 108 ] models of disease [ 153 ]. Initial observations identified an approximate 5-fold increase in Cx43 expression in biopsy material from individuals with diabetic nephropathy compared to healthy control [ 151 ], whilst paired-patch electrophysiology and ATP biosensing suggested that this increased expression was paralleled by diminished gap-junction intercellular coupling (GJIC) and increased hemichannel mediated ATP release [ 151 ].…”
Section: Cx43 Hemichannels and Treatment Of Inflammation In Diabetic Kidney Diseasementioning
confidence: 99%
“…Building on our published observations with Peptide 5, we recently assessed the efficacy of Danegaptide in conferring protection in an in vitro model of tubular injury. A Cx43 gap junction modifier [ 133 , 134 ], we reported that Danegaptide was also able to block hemichannel mediated dye uptake, ATP release and consequently TGFβ1 induced changes in markers of tubular injury e.g., E-Cadherin and N-Cadherin and fibrosis e.g., collagen-I, collagen-IV and fibronectin in human primary tubule epithelial cells (hPTECs) [ 135 ]. Furthermore, based on evidence that the Cx43 +/− UUO mouse presents with decreased fibroblast activation and diminished macrophage infiltration as compared to wild type UUO control [ 168 ], we employed proteome profiler arrays to screen for the expression profile of 125 inflammatory cytokines in TGFβ1 treated human primary proximal tubule cells in the presence/absence of Danegaptide [ 135 ].…”
Section: Cx43 Hemichannels and Treatment Of Inflammation In Diabetic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Despite their failure to decrease phenotypic disease burden, AAP10, rotagaptide, and danegaptide do alter the pattern of Cx43 expression, phosphorylation, GJ signaling, and hemichannel signaling [20,[72][73][74]. Studies have demonstrated that these peptides increase both Cx43 and Cx40 GJ signaling [72,75]. Unlike the peptides to be discussed later in this review, the AAP10 derivative peptides do not contain sequence homology with connexin proteins.…”
Section: Indirect Acting Peptides That Alter Gjs and Connexinsmentioning
confidence: 99%
“…Despite their failure to decrease phenotypic disease burden, AAP10, rotagaptide, and danegaptide do alter the pattern of Cx43 expression, phosphorylation, GJ signaling, and hemichannel signaling [17,[69][70][71]. Studies have demonstrated that these peptides increase both Cx43 and Cx40 GJ signaling [69,72]. Unlike the peptides to be discussed later in this review, the AAP10 derivative peptides do not contain sequence homology with connexin proteins.…”
Section: Indirect Acting Peptides That Alter Gjs and Connexinsmentioning
confidence: 99%